Analisis Relevansi Neurosains dengan Pembelajaran dan Kesehatan Spiritual - Mardiah Mardiah; Syaifuddin Sabda; Ani Cahyadi (Journal on Education, 2022)
The concept of learning from a neuroscience perspective is learning that empowers the brain's abilities by creating a learning environment that is challenging, fun, meaningful, and encourages students to be active. In the view of neuroscience, teachers and parents should develop learning strategies that are appropriate to the behavior, personality, development, and thinking of children as well as the ability or condition of their brains, especially in the learning process. The developed learning atmosphere is expected to stimulate children to be active in the learning process so that they do not feel bored and get a strong impression of the material or lesson content being taught by the teacher. Neuroscience provides basic knowledge for teachers and parents so that they can understand the biological basis of children, both from children's skills and from children's behavior, so that children can receive lessons optimally and learning objectives can be achieved optimally. Here, teachers and parents also get a comprehensive understanding of how to help children so that they can maximally develop their potential according to the stages of their development. In this study, the writers will examine the relationship between learning, spiritual health, and neuroscience, particularly from the standpoint of education, as well as the ideas that support it.